Multiple currencies and cross hedging - Udo Broll; Itzhak Zilcha (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
The paper derives optimal cross hedging and production rules for an exporting firm which faces multiple exchange rate risks. We study the impact of currency cross hedging upon the firm's export production for two countries. We demonstrate that when the forward market for cross hedging is unbiased there is a full hedge. However, the profits remain stochastic. The cross hedge reduces uncertainty about the producer's income except that part which is unhedgeable. Furthermore we show that introducing an unbiased forward market for a crosscurrency hedging will not affect the firm's total production level, even though it will increase the export to one of the two countries. This is in contrast to the usual impact which unbiased forward market has upon the risk-averse firm's production.
Keywords: F21; F31; 330; exports; cross hedging; forward markets